Large-scale converting waste coffee grounds into functional carbon materials as high-efficient adsorbent for organic dyes. (January 2019) - Wen, Xin; Liu, Hansong; Zhang, Lu; Zhang, Jing; Fu, Can; Shi, Xiaoze; Chen, Xuecheng; Mijowska, Ewa; Chen, Ming-Jun; Wang, De-Yi
Graphical abstract: Waste coffee grounds were catalytically carbonized into functional carbon materials and used as high-efficient adsorbent for organic dyes. Highlights: Biowaste coffee grounds were converted into functional carbon materials. The carbon yield was as high as 47.6 wt% via direct catalysis by 20 wt% FeCl3 . The synthesized carbon achieved high surface area and mesoporous structure. The functional carbon was effective for the removal of different dyes. The obtained carbon can be magnetically separated and reused multiple times. Abstract: Functional carbon materials have been fabricated through simple and effective catalytic carbonization with waste coffee grounds (CGs) as carbon precursor and FeCl3 as catalyst. The effect of FeCl3 loading and carbonization temperature on carbon yield was investigated. The morphology and structure of as-synthesized carbons was characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and nitrogen isothermal adsorption/desorption measurement, respectively. Furthermore, the carbon materials showed high efficiency for the removal of methylene blue (MB, 653.6 mg g −1 ), methyl orange (MO, 465.8 mg g −1 ) and rhodamine B (RB, 366.1 mg g −1 ). More importantly, the carbon was magnetic, so it can be easily separated by a magnet and reused multiple times. This work not only exploited a low–cost and large-scale preparation method to synthesize functional carbon materials from bioresources, but also provided an eco-friendly and effective adsorbent in water purification applications.